Simulasi Perhitungan Fuel Consumtion Pada Pesawat A320 Saat Holding Di Bandara Internatioanal Halim Perdanakusuma Menggunakan Teori Antrian - Dhimas, Dhimas Ilyas Ramadhani; Arifin, Mufti; Julizar, Ade (FTK UNSURYA, 2024)
In aircraft operations, to determine the amount of fuel consumption on the aircraft, it is necessary to know the time used for holding. Holding time is influenced by the number of aircraft using runway facilities and can be calculated using queuing theory. This study aims to determine the calculation of fuel consumption on aircraft when holding at Halim Perdanakusuma International Airport using queuing theory. Data for queue calculation is based on observations on flightradar24. Fuel consumption is estimated using aircraft maximum landing weight data, turning flight performance theory and aircraft manuals. From the results of the calculation, it was found that it took 6 minutes for the aircraft to queue during holding, from this time the fuel consumption calculation was carried out on the holding pattern and obtained the most fuel consumption results on the KOMIT holding pattern, which was 241,8 kg based on queuing theory and 554,8 kg based on actual data calculations. The difference in fuel consumption results is far due to the difference in time used. The time obtained based on queuing theory is 6 minutes and is equal for each holding pattern, while the time obtained based on actual data varies from one aircraft to another. For turning flight performance capabilities, the A320 aircraft can maneuver 180º within 1 minute with the largest radius of 9.204 m in 61 seconds or 1 minute 1 second on the IMU holding pattern and a radius of 2.327 m in 60,6 seconds or 1 minute 6 seconds on the COMMIT holding pattern.